Social psychological-pedagogical support of singleparent family - Ruslana Kazhuk; Liubov Shpilchak (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the definition of the concept of "incomplete family", describes the typology of single-parent families, the necessity of special social psychological and pedagogical support for children from such families and their parents has been proved. The analysis of various concepts of -support‖has been made. The idea of psychological and pedagogical support of modern incomplete families has been determined. Key words: incomplete family, types of single-parent families, support, social support, psychological and pedagogical support of single-parent families.